Anticonvulsant Effect of Alcea aucheri on Pentylenetetrazole and Maximal Electroshock Seizures in Mice - Mombeini, Tajmah (Basic Clin Neurosci, 2020)
INTRODUCTION: This study was designed to investigate the possible anticonvulsant effect of acute administration of an aqueous extract of flowers of Alcea aucheri (EFA) in two in vivo seizure models. METHODS: Seizures were induced in male adult Swiss mice by administration of Pentylenetetrazol (PTZ) or Maximal Electroshock (MES). Mice were randomly subjected to receive saline, EFA (8.75–175 mg.kg(−1)), or diazepam intraperitoneally (i.p.) 15 or 30 min before PTZ injection. In another experiment, mice were treated (i.p.) with saline, EFA (8.75–350 mg.kg(−1)), or phenytoin 15 or 30 min before the MES test. Diazepam and phenytoin were used as reference drugs. RESULTS: EFA (175 mg.kg(−1)) significantly increased the PTZ-induced seizure threshold compared with the saline control group 15 min after its administration. In the MES test, the extract (35 mg.kg(−1)) increased the latency to onset of tonic Hind Limb Extension (HLE) (seizure activity) compared with the saline group 15 min after treatment. Also, 30 min after treatment, EFA (35, 70, and 175 mg.kg(−1)) increased the latency to onset of the seizure, decreased the duration of the seizure (70 mg.kg(−1)), and decreased seizure occurrence (350 mg.kg(−1)) compared with those of the saline group. At both time points, the extract at all doses significantly reduced the mortality rate compared with the saline group. CONCLUSION: These findings provide evidence of a possible anticonvulsant effect of A. aucheri in PTZ and MES seizure models in mice.